PELATIHAN LITERASI MEDIA DENGAN METODE GETOK TULAR MULUT KE MULUT (STRATEGI WORD OF MOUTH COMUNICATION) UNTUK ANTISIPASI UJARAN KEBENCIAN (HATE SPEECH) SE KOTA DEPOK PROVINSI JAWA BARAT - Aulia Rahmawati; Krisnajaya Krisnajaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
Abstract Community Service is carried out by donating Training to anticipate the spread of hate speech before the 2019 Legislative Election and Presidential Election for high school students who are classified as beginner voters in Depok through media literacy with the Getok Tular word of mouth mouth Communication Strategy, which aims to develop strategies used to analyze and discuss hate speech messages in the media, build an awareness of the media as a